Sales organization effectiveness in Indonesia life insurance industry : moderating role of salesforce automation - Syahputra (2017)
Sales organization effectiveness is a crucial factor of a successful company performance that can be enhanced by having an effective salesforce and technology. The present study was designed to examine the relationship between salesforce management, sales management control strategy, salesforce characteristics and sales organization effectiveness with salesforce automation as a moderating variable. The study was carried-out in life insurance companies in Indonesia. The study used the agency theory and the contingency theory to determine sales organization effectiveness. The quantitative approach was mainly used in this study. In order to achieve the main objectives of this study, data were collected from sales managers of life insurance in Indonesia. Hierarchical regression analysis was then conducted to examine the moderating effects of the salesforce automation on the relationship between salesforce management, sales management control strategy, salesforce characteristics and sales organization effectiveness. The results of the regression analysis revealed that salesforce performance, sales management control strategy and salesforce characteristics were positively associated with sales organization effectiveness. Moreover, the findings showed that salesforce performance, sales management control strategy and salesforce characteristics had a stronger effect on sales organization effectiveness. Furthermore, the results also showed that salesforce automation plays an important role in moderating the relationship between sales management control strategy and sales organization effectiveness. However, salesforce automation did not moderate the relationship between salesforce performance and salesforce effectiveness on sales organization effectiveness respectively. The study may contribute to the body of knowledge on sales management. Furthermore, it would be beneficial to the Indonesian life insurance industry to manage their salesforce better and be more focused on sales technology.